2020
DOI: 10.1002/ehf2.13070
|View full text |Cite
|
Sign up to set email alerts
|

Predominant subtype of heart failure after acute myocardial infarction is heart failure with non‐reduced ejection fraction

Abstract: Aims Patients who survive acute myocardial infarction (AMI) are at risk of being rehospitalized owing to the occurrence of acute decompensated heart failure (HF). However, the clinical characteristics of HF after AMI, especially the frequency of each HF subtype, are unclear. Methods and results We retrospectively studied 1055 patients with AMI. We excluded 257 patients, who were admitted >48 h after the onset of AMI, died during hospitalization or after discharge, and whose echocardiogram data at index hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 22 publications
1
10
0
1
Order By: Relevance
“…With the extension of life expectancy and the reduction in in-hospital mortality, nonfatal events after ACS strongly affect the patients' quality of life and significantly increase their mortality [21][22][23]. A recent study [24] showed that 1 out of 10 patients with ACS discharged from the hospital will suffer at least one readmission for HF within the first 5 years after ACS, which is much higher than the incidence of other complications, such as major bleeding [25,26] or stroke events [27].…”
Section: Discussionmentioning
confidence: 99%
“…With the extension of life expectancy and the reduction in in-hospital mortality, nonfatal events after ACS strongly affect the patients' quality of life and significantly increase their mortality [21][22][23]. A recent study [24] showed that 1 out of 10 patients with ACS discharged from the hospital will suffer at least one readmission for HF within the first 5 years after ACS, which is much higher than the incidence of other complications, such as major bleeding [25,26] or stroke events [27].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, we also reported the frequency of the occurrence of HF subtypes after PCI, and HFpEF accounted for the largest proportion of newly diagnosed HF. Another study also indicated that the predominant subtypes of HF after AMI were HFmrEF and HFpEF, or HF with non-reduced EF ( 13 ). With the increase of population aging and the increased survival rate after MI, the prevalence of HF continues to rise, among which HFpEF has become the predominant type ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent CVOTs that were initially conducted among patients with heart failure with reduced ejection fraction (HFrEF), and subsequently among patients with heart failure with preserved ejection fraction (HFpEF), SGLT2i reduced the incidence of HHF by approximately 30% and improved heart-failure specific endpoints such as Kansas City Cardiomyopathy Questionnaire scores and N-terminal pro b-type natriuretic peptide levels [7]. However, these trials did not assess MACE endpoints such as MI or stroke hospitalizations [8][9][10], which are major contributors to cardiovascular morbidity and mortality among HFrEF and HFpEF patients [11,12].…”
Section: Introductionmentioning
confidence: 99%